Perceived procedural rationality and political behaviours in strategic decision making process and organizational commitment triangle - (:unkn) unknown (ELSEVIER SCIENCE BV, 2011)
Effectiveness of a strategic decision is characterized with the strategic decision making process behind it. To follow a rational process; looking for and analyzing relevant information extensively; giving adequate importance to analytic techniques and focusing on crucial information rather than irrelevant ones should be realized. To protect the process from political behaviours; decision makers should primarily be concerned with organizational goals and open with each other about their interests and preferences; make negotiation among group members and should not effect the decision with their own power and influence. Today's universities are not only expected to research and teach; but also make their own strategic plans for future. With these expectations, considering the fact that strategic decision making process determine not only the final decisions; but also effect the people for whom decisions are; a relation between perceived procedural rationality, political behaviours and organizational commitment were hypothesized. The study was conducted with 150 academicians and data were analyzed with regression analyze. (C) 2011 Published by Elsevier Ltd. Selection and/or peer-review under responsibility 7th International Strategic Management Conference
Keywords: Strategic decision making process; Rationality; Political behaviour; Organizational commitment; MANAGEMENT; TACTICS